SURAH AL-FATIHAH: SEBUAH TAFSIRAN PERSPEKTIF SEMIOTIKA BAHASA - Ulin Nuha (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2012)
The Qur'an is the word of God is holy, the message contained therein Ilahiyah . Al-Qur'an is it self a form of communication in the form of verbal language of God to his servant. In order to understand the message language, then we must be interpret these verbal symbols. This is the actual function of semiotics, which is it serves as a knife from the symbol. Semiotics of signifier, and the signified. In this respect semiotics will be used to dissect the message symbols of the Surah Al-Fatihah. So what exactly, what is message of God is known that on language symbols verse (al-Fatihah).